The Effect of Toxic Workplace Environment and Job Burnout on Turnover Intention (Study: PT Steel Pipe Industry of Indonesia, Tbk – Unit V) - Monica, Hesty; Ratna Hayati, Neuneung (Journal of Accounting and Finance Management, 2025)
The main objective of this research is to explain the influence of a toxic workplace environment and job burnout on employee turnover intention at PT. Steel Pipe Industry of Indonesia, Tbk – Unit Karawang. Furthermore, this research aims to identify the influence of a toxic workplace environment and job burnout on employee turnover intention levels at PT. Steel Pipe Industry of Indonesia, Tbk – Unit Karawang. This research uses a quantitative approach and descriptive analysis, with a sample of 110 respondents. Data collection efforts in this research were carried out using a survey method in the form of a questionnaire. The results of multiple linear regression equation modeling were obtained using SPSS for Windows software. The research results show that toxic workplace environment and job burnout have a positive effect on turnover intention. The findings in this research will help company management, policy makers and practitioners to formulate policies to reduce toxic workplace environments, job burnout and turnover intention among company employees.